2010
DOI: 10.1200/jco.2009.24.4798
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Risk of Distant Recurrence Using the 21-Gene Recurrence Score in Node-Negative and Node-Positive Postmenopausal Patients With Breast Cancer Treated With Anastrozole or Tamoxifen: A TransATAC Study

Abstract: PURPOSE To determine whether the Recurrence Score (RS) provided independent information on risk of distant recurrence (DR) in the tamoxifen and anastrozole arms of the Arimidex, Tamoxifen, Alone or in Combination (ATAC) Trial. PATIENTS AND METHODS RNA was extracted from 1,372 tumor blocks from postmenopausal patients with hormone receptor-positive primary breast cancer in the monotherapy arms of ATAC. Twenty-one genes were assessed by quantitative reverse transcriptase polymerase chain reaction, and the RS was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
458
4
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 651 publications
(485 citation statements)
references
References 18 publications
16
458
4
7
Order By: Relevance
“…The recurrence score has been shown to correlate with risk of both loco-regional 23 and distant recurrence in ER-positive, node-negative breast cancer. 24,25 Furthermore, this 21 multigene assay is predictive of treatment response to endocrine therapy when the recurrence score is low and to chemotherapy when the recurrence score is high. 26,27 Proliferation-related genes receive the highest weighting in the algorithm and consequently make the greatest contribution to the determination of the recurrence score.…”
Section: Lp Feeley Et Almentioning
confidence: 99%
“…The recurrence score has been shown to correlate with risk of both loco-regional 23 and distant recurrence in ER-positive, node-negative breast cancer. 24,25 Furthermore, this 21 multigene assay is predictive of treatment response to endocrine therapy when the recurrence score is low and to chemotherapy when the recurrence score is high. 26,27 Proliferation-related genes receive the highest weighting in the algorithm and consequently make the greatest contribution to the determination of the recurrence score.…”
Section: Lp Feeley Et Almentioning
confidence: 99%
“…Two recent studies showed that patients with node-positive and ER-positive breast cancer had clinically significant (Ͼ10%) risk of relapse for any 21-gene recurrence score class [5,9]. In one study, the low or intermediate recurrence score identified a subset of patients for whom chemotherapy offered no significant benefit over tamoxifen alone, but the recurrence score failed to identify any subset with excellent survival from either treatment arm [5].…”
Section: Chemosensitivity Endocrine Sensitivity and The Concept Of mentioning
confidence: 99%
“…The test is most useful in patients with hormone receptor-positive, her2-negative, lymph node-negative cancer. Studies have retrospectively evaluated the use of Oncotype dx in patients with lymph node-positive cancer, but those studies are not entirely robust from a statistical standpoint 19,20 .…”
Section: Patient and Disease Characteristics And Recurrence Riskmentioning
confidence: 99%